Considerations of Quality in Phenomenographic Research - Samantha Sin (International Journal of Qualitative Methods, 2010)
In this paper the author considers issues of quality in phenomenographic research. Research rigor, which is traditionally evaluated by validity and reliability criteria, ensures that research findings reflect the object of study. Quality in research subsumes rigor and extends considerably beyond satisfying the criteria for rigor. A piece of research has to convince readers of its quality when evaluated against criteria that have been developed through contributions and agreements within the research community. This paper tackles the quality issue in phenomenographic research in three steps. First, criteria for quality in qualitative research are discussed. Second and drawing on the literature, related issues when the criteria are applied to phenomenographic studies and the ways of addressing the issues are examined. Finally, the phenomenographic process is analyzed and suggestions are made for enhancing quality at each stage of the process. New phenomenographic researchers especially will find this paper as a useful guide.